Women's Education and Fertility in China - Zheyuan Zhang; Zhong Zhao (Institute of Labor Economics (IZA), 2023)
Using data from the China Family Panel Studies, this paper exploits the Compulsory Education Law of China implemented in the 1980s to empirically examine the causal impact of women's education on fertility in rural China by difference-in-differences methods. The results show that an additional year of schooling lowered the number of children a woman would have by approximately 0.09 children, postponed the age of first childbirth by 0.7 years, and reduced the probability of having a second child or more children by 0.18 among those mothers whose first child was a girl. In addition to the income effect, these results are also partly explained by more educated women preferring quality to quantity of children, placing a greater value on leisure and no longer perceiving children as the sole focus in their lives.
Keywords: I25; J11; J13; 330; compulsory education law; demographic transition; fertility; women's education; quality and quantity of children